Trail log - 2021 - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2021)
Summary: Death of our son, Giles Campbell Rolston, in January, and in August scattered his cremated remains on a trail in Rocky Mountain National Park on which he and I had once done a 30 mile, ten day backpack. Covid 19 vaccinations. Blizzard in March. Wildflowers. Pasqueflower at Easter. Spring birding. June - tornado in Weld County. August - video presentation, Shangdong, China. October - video: "From Shenandoah to the Mountain West," Yosemite. December, wind gusts above 100 mph.
Keywords: personal narrative